Performing Ethnomusicology : Teaching and Representation in World Music Ensembles - Solís, Ted (Book collections on Project MUSE., 2004)
'Performing Ethnomusicology' deals exclusively with creating, teaching, and contextualizing academic world music performing ensembles. 16 essays discuss the problems of public performance and the pragmatics of pedagogy and learning processes.